PREDICTION OF THE IMPACTS OF CLIMATE CHANGES ON THE STREAM FLOW OF AJALI RIVER WATERSHED USING SWAT MODEL (Nigerian Journal of Technology, 2017)
Soil, Water Analysis Tool, (SWAT) model was used to predict the impacts of Climate Change on Ajali River watershed, Aguobu-Umumba, Ezeagu, Enugu State, Nigeria. The model was first used to simulate stream flow using observed data. After model run, parameterization, sensitivity analysis, the monthly coefficients of determination (R2) were 0.5739 and 0.6776 for calibration and validation respectively. Having performed fairly well, the model was thereafter run to simulate climate change impacts on streamflow. Two GCMs - CCCMA and GFDL, were used to generate future climate data and run in SWAT. Total observed streamflow for the baseline (1981-2000) was compared with that predicted (2046 – 2064) from the GCMs. The results of the CCCMA models showed an increase of 383.72m3/s and 2.1% in the streamflow of the Ajali river watershed when projected to 2046 – 2064 as against the historical baseline while GFDL showed 3358.58 m3/s and 18.9% respectively. The study, when applied, will help watershed managers and planners in the management of the watershed for effectiveness and efficiency. It will also increase our awareness of the effect of climate change on other water bodies in the hinterlands. http://dx.doi.org/10.4314/njt.v36i4.39